The Relationship of Curriculum, Teaching Methods, Assessment Methods, and School and Home Environment with Learning Difficulties in English Language from the Studetns’ Perspectives - Mohmmad Khasawneh (Journal of Innovation in Educational and Cultural Research, 2022)
This study aimed to identify the relationship between curriculum, teaching methods, and assessment methods, and school and home environment and learning difficulties in English language among students in the elementary stage in Irbid Governorate from the students’ point of view. The study used the descriptive-analytic approach. The sample of the study consisted of (100) male and female students, who teach the fourth and fifth grades, distributed as follows: (50) males and (50) females. To achieve the objectives of the study, a questionnaire was designed to identify the relationship between curriculum, teaching methods, and assessment methods, and school and home environment and learning difficulties among students in English language. The questionnaire included the following dimensions, curriculum, teaching methods, and assessment methods, and school and home environment. The results of the study revealed that the overall degree for the relationship between curriculum, teaching methods, and assessment methods, and school and home environment to students’ learning difficulties In English language at the primary stage from the students’ point of view was high in all dimensions of study. The study concluded that it is important to identify the importance of curriculum, teaching methods, and assessment methods, and school and home environment for students with LDs and students should be aware of these factors and their role.